A global biological conservation horizon scan of issues for 2023. (January 2023) - Sutherland, William J.; Bennett, Craig; Brotherton, Peter N.M.; Butterworth, Holly M.; Clout, Mick N.; Côté, Isabelle M.; Dinsdale, Jason; Esmail, Nafeesa; Fleishman, Erica; Gaston, Kevin J.; Herbert-Read, James E.; Hughes, Alice; et al.
Abstract: We present the results of our 14th horizon scan of issues we expect to influence biological conservation in the future. From an initial set of 102 topics, our global panel of 30 scientists and practitioners identified 15 issues we consider most urgent for societies worldwide to address. Issues are novel within biological conservation or represent a substantial positive or negative step change at global or regional scales. Issues such as submerged artificial light fisheries and accelerating upper ocean currents could have profound negative impacts on marine or coastal ecosystems. We also identified potentially positive technological advances, including energy production and storage, improved fertilisation methods, and expansion of biodegradable materials. If effectively managed, these technologies could realise future benefits for biological diversity. Highlights: Our 14th annual horizon scan identified 15 emerging issues of concern for global biodiversity conservation. A panel of 30 scientists and practitioners submitted a total of 102 topics that were ranked using a Delphi-style technique according to novelty and likelihood of impact on biodiversity conservation. The top 36 issues were discussed in person and online in September 2022 during which issues were ranked according to the same criteria. Our 15 issues cover impacts from DNA-enabled biobatteries to submerged artificial light fisheries. Other emerging issues include increased demand for chitosan, accelerating upper ocean currents, and microbiome stewardship.